Molecular genetics of colon cancer. - Tomlinson, I; Ilyas, M; Novelli, M (1997)
Colorectal cancer remains a major health problem. Few therapies are effective apart from surgery, and survival has increased little in recent years. This is despite the fact that screening by colonoscopy can potentially remove nearly all colorectal tumours before they become malignant. Molecular genetics has identified some inherited mutations (such as at APC and the mismatch repair loci) that predispose to colon cancer and some somatic mutations (such as at APC and p53) that cause sporadic colon tumours. We review the likely role of these and other genes in colorectal tumorigenesis. We also highlight areas of relative ignorance in colon cancer and emphasise that many important genes, especially those that cause invasion and metastasis, remain to be identified. Colorectal cancer is, however, a well characterised tumour, as regards both its natural history and its histopathology; there are consequently good prospects for advances in colon cancer genetics, with probable benefits for its treatment. We anticipate: (a) that new genes predisposing to colon tumours, including those conferring relatively minor risks, will be characterised; (b) genes and proteins important in invasion and metastasis will be identified; (c) the network of protein interactions in which molecules such as APC are involved will be elucidated; (d) large-scale studies of somatic mutations in tumours will provide accurate predictions of prognosis and suggest optimal therapeutic regimens; and (e) new potential targets for therapy will be identified. Whilst molecular genetics is by no means sufficient for progress in preventing and treating colon cancer, it is a necessary and central part of such advances.